2020
DOI: 10.1088/1757-899x/912/5/052012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mechanical behavior for animal fiber Reinforced hybrid fiber composite for marine application

Abstract: When natural fibers are bonded together with synthetic material, they exhibit increased mechanical properties which are environment friendly and of low cost. The application of natural fibers as a substitute for chemical fibers draws great interest due to its less weight, lower raw material price, and ecological benefits of using green resources which are biodegradable and renewable. By combining these natural fibers in different compositions, the above-mentioned properties can be enhanced. In this investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The composite is manufactured in physical fabrication by hand layup [12,14]. The plain square surface is chosen as the pattern dimension (300 × 300 × 3.5 mm3), over which a layer of wax is coated to release the composite removal after the manufacturing process.…”
Section: Composite Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…The composite is manufactured in physical fabrication by hand layup [12,14]. The plain square surface is chosen as the pattern dimension (300 × 300 × 3.5 mm3), over which a layer of wax is coated to release the composite removal after the manufacturing process.…”
Section: Composite Fabricationmentioning
confidence: 99%
“…Now the first layer of Kevlar bidirectional fiber is placed into the die, and epoxy resin with a hardener is rolled over the thread; a hand roller is used to move and distribute epoxy resin uniformly over the fiber. The process is repeated until the completion of all layer formation sequences (Kevlar Human hair (X-direction) +Kevlar+ Human hair (Y-direction) +Kevlar) by hand layup method [2,12,14]. Finally, a constant load (20 Kg) is applied to it for the uniform formation of epoxy resin, and then it is dried out at room temperature for 24 h. After a few days, a cured sample is cut into small sizes for testing [4,10].…”
Section: Composite Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinesh et al [13] examine the natural fiber composites made from hen, goat hair fiber, human hair, Kevlar followed by the tensile, flexural and water absorption test. It was found that the sample made from the composition of Kevlar and human hair had resulted in the best sample for tensile and flexural applications as it generated very high values of strength.…”
Section: Kevlar -Natural Fiber Compositesmentioning
confidence: 99%
“…The animal fiber like goat hair (diamond hair) possesses great insulating property and elasticity, moisture-wicking property. Goat fiber is one of the most expensive fibers among animal fibers (Dinesh et al , 2020). Table 2 represents the mechanical properties of various natural fibers.…”
Section: Natural Fiber For Bio-composites Its Classifications and App...mentioning
confidence: 99%